2021
DOI: 10.3389/fcell.2021.672335
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Causes Endothelial Dysfunction via Inflammatory Factor-Mediated Activation of Epithelial Sodium Channel (ENaC)

Abstract: BackgroundHyperhomocysteinemia (HHcy) causes cardiovascular diseases via regulating inflammatory responses. We investigated whether and how the epithelial sodium channel (ENaC), a recently identified ion channel in endothelial cells, plays a role in HHcy-induced endothelial dysfunction.MethodsCell-attached patch-clamp recording in acute split-open aortic endothelial cells, western blot, confocal imaging, and wire myograph combined with pharmacological approaches were used to determine whether HHcy-mediated inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Hcy post-translationally downregulates dimethylarginine dimethylaminohydrolase enzyme activity (the enzyme that degrades ADMA), causing asymmetric dimethylarginine (ADMA, an endogenous inhibitor of NO synthase) to accumulate and thus inhibit NO synthesis [84]. Liang et al (2021) described that Hcy activates the epithelial sodium channel and consequently induces endothelial dysfunction via reactive oxygen species (ROS)/COX-2-dependent activation of SGK-1/Nedd4-2 signaling [85]. Additionally, Hcy induced a calcium-mediated disruption of dynamics and mitochondrial function in endothelial cells due to overexpression of the mitochondrial calcium uniporter and the IP3R-Grp75-VDAC complex in mitochondria-associated membranes [86].…”
Section: Hcy-induced Endothelial Dysfunctionmentioning
confidence: 99%
“…Hcy post-translationally downregulates dimethylarginine dimethylaminohydrolase enzyme activity (the enzyme that degrades ADMA), causing asymmetric dimethylarginine (ADMA, an endogenous inhibitor of NO synthase) to accumulate and thus inhibit NO synthesis [84]. Liang et al (2021) described that Hcy activates the epithelial sodium channel and consequently induces endothelial dysfunction via reactive oxygen species (ROS)/COX-2-dependent activation of SGK-1/Nedd4-2 signaling [85]. Additionally, Hcy induced a calcium-mediated disruption of dynamics and mitochondrial function in endothelial cells due to overexpression of the mitochondrial calcium uniporter and the IP3R-Grp75-VDAC complex in mitochondria-associated membranes [86].…”
Section: Hcy-induced Endothelial Dysfunctionmentioning
confidence: 99%
“…Moreover, our data link VCDD to enhancement of norepinephrineinduced contraction probably due to altered biomechanical properties of the aorta as well as impairment of acetylcholine-relaxation. Supporting this notion, Hcy was shown to be associated with endothelial dysfunction (Liang et al, 2021), and the combination of HCD and methionine, a precursor of Hcy, results in virtually abolished endothelium-dependent relaxation (Zulli et al, 2003). Furthermore, VCDD leads to atherogenic transformation of the aorta already in the absence of HCD.…”
Section: Discussionmentioning
confidence: 91%
“…The biophysical features of endothelial EnNaC single-channel current, recorded in split-open MAs and in MAECs shown in this study, are comparable to those described previously in the rat or mouse endothelial cells ( Liu et al, 2015b ; Niu et al, 2021 ). Indeed, EnNaC plays a role in salt overload-, homocysteinmia-, and high-fat diet-induced vascular dysfunction ( Yang et al, 2020b ; Liang et al, 2021 ; Niu et al, 2021 ). In addition, other reports showed that activation of EnNaC is responsible for endothelial stiffness and vascular remodeling ( Guo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased production of vasodilator NO is tightly linked to endothelial dysfunction, vasoconstriction, and elevation of blood pressure. Previous studies showed that activation of EnNaC in the endothelium contributes to pathological stimuli-induced vascular endothelial dysfunction and hypertension ( Jeggle et al, 2013 ; Wang et al, 2018 ; Yang et al, 2020b ; Liang et al, 2021 ). Augmented EnNaC activity hampered the transportation of L-arginine, resulting in impaired NO generation in human umbilical vein endothelial cells ( Guo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%